Proposal of a model for the analysis of a text as a communicative event (1995)
An attempt has been made to present a model for the analysis of a text as a communicative evento The presupposition underlying this task is that it is actually possible and to some extent desirable - to construct a 'model'as a descriptive device, powerful enough to account for the text as the linguistic unit of the communicative interaction. The different components of the model (Sender, Receiver, Text, Text Levels, Competences, Socio-Psychological characterization of participants, and Context) are described, as well as their functioning and interaction. Then the model is applied for the analysis of a text ('A Sticky Problem'), and some conclusions are drawn on the model as a whole, its advantages and shortcomings.